2008
DOI: 10.1038/ncb1795
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding function of PAK in the PDK1–Akt pathway

Abstract: Many extracellular signals stimulate phosphatidylinositol-3-kinase, which in turn activates the Rac1 GTPase, the protein kinase Akt and the Akt Thr 308 upstream kinase PDK1. Active Rac1 stimulates a number of events, including substrate phosphorylation by a subgroup of the PAK family of kinases. The combined effects of Rac1, PDK1 and Akt are crucial for cell migration, growth, survival, metabolism and tumorigenesis. Here we show that Rac1 stimulates a second, kinase-independent function of PAK1. The PAK1 kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 30 publications
10
197
0
Order By: Relevance
“…Partial inhibition of Pak activity by PAK18 did not alter Akt activation, which may be due to a kinase-independent mode of Akt activation by Pak as reported recently (Higuchi et al, 2008). The preferential control of Mek activation by Pak1 and of Akt activation by Pak2 suggests that cell type-specific expression of Pak1 and Pak2 will result in cell type-specific effects of Rac1 on Mek1 and Akt, respectively.…”
Section: Rac1 In Skin Tumorssupporting
confidence: 71%
See 1 more Smart Citation
“…Partial inhibition of Pak activity by PAK18 did not alter Akt activation, which may be due to a kinase-independent mode of Akt activation by Pak as reported recently (Higuchi et al, 2008). The preferential control of Mek activation by Pak1 and of Akt activation by Pak2 suggests that cell type-specific expression of Pak1 and Pak2 will result in cell type-specific effects of Rac1 on Mek1 and Akt, respectively.…”
Section: Rac1 In Skin Tumorssupporting
confidence: 71%
“…Rac1 was reported to promote RafMek-Erk signaling by Pak-mediated phosphorylation of Raf at serine 338 (King et al, 1998), or of Mek1 at serine 298 (Slack-Davis et al, 2003), by promoting interaction between Mek and Erk (Eblen et al, 2002), by direct interaction of Rac1 with Erk (Sundberg-Smith et al, 2005) and by controlling the nuclear translocation of Erk (Hirsch et al, 2002). With respect to PI3K signaling, Rac1 was shown to be upstream (Keely et al, 1997) and downstream of PI3K signaling (Hawkins et al, 1995), and the Rac1 effector, Pak1, was shown to activate Akt by direct interaction, independent of the kinase function of Pak (Higuchi et al, 2008). However, although Rac1 activation was found to promote cell survival by activation of Akt, Erk and NF-kB, it can also induce apoptosis by stimulation of p38 and JNK (Xia et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Rac1 stimulates Akt activity through a kinase-independent scaffolding function of PAK1 34 . We then assessed the possible involvement of PAK1 in blebbistatininduced Akt activation.…”
Section: Nature Communications | Doimentioning
confidence: 99%
“…We then assessed the possible involvement of PAK1 in blebbistatininduced Akt activation. PAK1(N-SP) (the N-terminal fragment of PAK1, 1-205aa, with the substitution of Ser76 with proline), a dominant-negative mutant disrupting the scaffolding function of PAK1 34 , effectively abolished the effect of blebbistatin to activate Akt (Fig. 4g).…”
Section: Nature Communications | Doimentioning
confidence: 99%
“…An attractive hypothesis is the existence of cofactors working in conjunction with TM phosphorylation. Akt-binding proteins, such as Hsp90 (Sato et al, 2000;Basso et al, 2002), TRB3 and PAK (Du et al, 2003;Du and Tsichlis, 2005;Higuchi et al, 2008), have been reported to regulate negatively or positively the phosphorylation status of Akt. It would be interesting to evaluate the relationship between their binding ability and TM phosphorylation.…”
Section: Regulation Of A-loop Phosphorylation Via Tm Phosphorylation mentioning
confidence: 99%